Wireless Monitoring System for Miniature Flexible Tank Performance - Yazid, Najwa; Muhammad Razif, Muhammad Rusydi; Mohd Shah, Nor Shahida (Progress in Engineering Application and Technology, 2022)
The Internet of Things (IoT) had grown faster widely through the global for its applications to the living. The IoT implemented in the logistics industry in order to build a smart logistic system that contributes to the security and efficient monitoring system as currently, there is lack of efficient wireless monitoring system that can provide real-time data of container’s surrounding in order to ease the management of goods. This thesis will present a thorough development process of the prototype of the wireless monitoring system for MyFlexible tank performance that will highlight the implementation of sensors, microcontroller, and Blynk server. Blynk is an example of IoT server that provides an application for user to monitor their respected system that has been programmed into the microcontroller and linked to its server. The system will work with various sensors to sense any changes on the tank’s surrounding and data will be transmitted to the server. The data then will be displayed over the Blynk application which allows the user to monitor the data in real-time. However, the system has a limited operational system which required a Wi-Fi connection linked to the microcontroller. This project is expected to provide an efficient monitoring system to be implemented in the real application of flexible tank. Hence, it will ease the management of supply to monitor their packages in real-time.